The fairies encyclopedia - Bazaldua, Barbara (DK, 2012)
"With a sprinkling of pixie dust, it's time to fly off to Never Land! Peek inside this magical encyclopedia to discover everything you ever wanted to know about Tinker Bell and all your favorite Disney Fairies."--P. [4] of cover.